Study Of Serum Total Sialic Acid Level And Its Correlation With Atherogenic Index In Cases Of Acute Myocardial Infarction - ANUJ PARKASH; PARUL SINGLA; MAMTA SETH; H. K. AGARWAL; SHASHI SETH (International Journal of Pharma and Bio Sciences, 2011)
Sialic acid, an acylated derivative of nine carbon sugar neuraminic acid. Serum total sialic acid is a cardiovascular risk factor and associated with increased cardiovascular mortality. The present study was planned to explore the role of serum total sialic acid levels and its correlation with atherogenic index in acute myocardial infarction. It was a case controlled study conducted in the Department of Biochemistry, Pt B D Sharma PGIMS, Rohtak. 35 patients of myocardial infarction were placed in study group and 35 healthy volunteers in the control group. Serum Sialic acid was analyzed by Warren’s TBA method. Serum total sialic acid levels were found to be significantly high in study group. A strong positive correlation was observed between atherogenic index and sialic acid levels in study group. Elevation in serum total sialic acid level might result either due to the cell damage after acute myocardial infarction or increase in sialidase activity.